Fibronectin-mediated binding of group A streptococci to human polymorphonuclear leukocytes. - Simpson, W A (1982)
Human plasma was shown to promote the attachment of an avirulent strain of Streptococcus pyogenes to human polymorphonuclear leukocytes. Removal of the fibronectin by absorption of the plasma with agarose-immobilized gelatin abolished the attachment-promoting activity. The activity of the absorbed plasma was restored with purified human serum fibronectin. The fibronectin was found to promote the attachment of three M protein-negative, but not of three M protein-positive, strains of streptococci. Radiolabeled fibronectin was shown to bind in various degrees to all strains of S. pyogenes tested. Thus, in the absence of streptococci surface M protein, fibronectin promotes the association of group A streptococci with human polymorphonuclear leukocytes.